TINJAUAN HISTORIS LINTASAN JEMAAT GEREJA PROTESTAN DI INDONESIA BAGIAN BARAT (GPIB) JEMAAT MARTURIA LAMPUNG TAHUN 1937-1994 - Mariani Magdalena Sibarani; Aurora Nandia Febrianti; Ozi Hendratama (Universitas Batanghari Jambi, 2026)
This research explores the historical trajectory of the Protestant Church in Western Indonesia (GPIB) Marturia Congregation in Lampung from 1937 to 1994. The study aims to uncover the formation history of GPIB Marturia and its development in terms of fellowship, ministry, and Christian witness in the Lampung region. Using historical methods including heuristics, verification, interpretation, and historiography the research draws on primary sources such as church archives, documents, and interviews with church figures. The findings reveal that the church was initially established as part of De Protestantsche Kerk in Nederlands-Indie and later developed into GPIB Marturia through various historical dynamics. Beyond serving as a place of worship, this church stands as a significant historical symbol in Bandar Lampung and has been recognized as a cultural heritage site. This study is expected to contribute to the preservation of local church history and provide insights into the importance of understanding the church’s historical journey as part of local identity and cultural legacy